Early Management of Shock Condition in STEMI Patient - Nugraha, Yudha Tria; Anjarwani, Setyasih; Satrijo, Budi; Rohman, Mohammad Saifur (Universitas Brawijaya, 2023)
Background: Acute myocardial infarction is one of the emerging cardiovascular events worldwide. Infarcts of the inferior wall were present between one-third and half of the patients with RV involvement. The worse outcome was strongly associated with cardiogenic shock, and 7% of cases were caused by RV failure.Objective: This study aimed to describe the diagnosis and management of cardiogenic shock in STEMICase presentation: A male in his 40s was brought to our hospital 12 hours after the onset of persistent epigastric pain. He had a history of hypertension and a family history of diabetes Mellitus. Diagnostic procedures included blood tests, ECG, X-rays, coronary angiogram, and echocardiography. He underwent PCI to implant DES in his proximal RCA, which had 100% occlusion. The patient was admitted to the intensive cardiovascular care unit for 30 hours and died due to various complications.Conclusion: Current case was very complicated and seriously life-threatening. After acute myocardial infarction, Important problems kept coming up one after the other, and they all affected each other. Patients with cardiogenic shock must be found quickly and treated quickly and aggressively.